Theoretical and applied rheology : proceedings of the XIth International Congress on Rheology, Brussels, Belgium, August 17-21, 1992 - Moldenaers, P.; Keunings, R. (Elsevier, 1992)
More than 900 authors from over 35 countries contributed to the 1992 International Congress on Rheology. These proceedings volumes comprise 17 plenary and keynote papers, 250 oral contributions and some 200 poster presentations. All relevant aspects of rheology are covered, e.g., theoretical rheology, molecular theories, fluid mechanics, rheometry, experimental methods, foams, polymer solutions, polymer melts, rubber, solids, composites, biorheology, industrial rheology, polymer processing, food rheology and electrorheology, reflecting the development of rheology into a broad, multidisciplinar.